Jemma Kidd make-up secrets - Kidd, Jemma, 1974- (St. Martin's Press, 2012)
"Jemma Kidd's philosophy is that make-up should be used cleverly and sparingly to bring out a woman's natural beauty, enhancing her best features and disguising any perceived imperfections. In Jemma Kidd Make-Up Secrets, she shows you how. In Part 1: Making Make-Up Work for You, Jemma demystifies the new wonder products in the market, and shows how to use and apply them. She demonstrates how to achieve a flawless complexion and bring out the best in every face shape, and how to make up eyes and lips depending on your face and eye shape, age, coloring, and overall style. In Part 2: The Problem Solver, Jemma addresses all the main beauty concerns of every woman--how to take care of your skin, how to look younger, how to keep your makeup up-to-date, and how to cope with environmental onslaughts like the damaging effects of the sun and cold weather. Also included are ten great eye and lip combinations, a tutorial on how to achieve iconic looks--from Kate Moss to Audrey Hepburn, plus a fail-safe, five-minute makeup regime for whenever you're pressed for time and much more. Beautifully photographed and designed, this book offers expert advice in an accessible way, with informative text in bite-size chunks, quotes, tips, top tens, insider secrets, and practical step-by-step instructions--all the know-how to create the perfect look for every occasion"--